2023
DOI: 10.22270/ujpr.v8i1.900
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Status of Hepatitis B Virus Infection Among Freshmen University Students in Yemen

Abstract: Background: Hepatitis B virus (HBV) is a most important health problem, it's a global pandemic. Previous surveys showed a high prevalence of hepatitis B infection in Yemen. Hepatitis B vaccination is the most efficient way to prevent hepatitis B virus infection and its outcomes (such as hepatocellular carcinoma, cirrhosis, and liver failure). Aim: To measure the immune status of hepatitis B virus amongst first-year students at the faculties of Thamar University during the academic year 2021-2022. Methods: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Low HBV prevalence in Saudi Arabia indicates the role of vaccination and educational programs to eliminate HBV infection among HCWs. Previous studies have shown that the needle stick injury (NSI) was the key risk factor of HBV infection among HCWs [22,20,28,24,21,29,25] In Yemen, the prevalence of HBV infection varied from town to town as Taiz and Sana , a and reduced from year to year, as indicated through many studies [22,25,24]. The HBV prevalence reduced from 9.9% [22] to 2.76% [25].…”
Section: Discussionmentioning
confidence: 99%
“…Low HBV prevalence in Saudi Arabia indicates the role of vaccination and educational programs to eliminate HBV infection among HCWs. Previous studies have shown that the needle stick injury (NSI) was the key risk factor of HBV infection among HCWs [22,20,28,24,21,29,25] In Yemen, the prevalence of HBV infection varied from town to town as Taiz and Sana , a and reduced from year to year, as indicated through many studies [22,25,24]. The HBV prevalence reduced from 9.9% [22] to 2.76% [25].…”
Section: Discussionmentioning
confidence: 99%